Buscando a qualidade da informação produzida pelo e-sus ab: influências, dificuldades e perspectivas dos gestores em saúde - Albuquerque, Saemmy Grasiely Estrela de (2017)
ALBUQUERQUE, S. G. E. Seeking the quality of information produced by e-SUS AB: influences, difficulties and perspectives of health managers. 2017. 126f. Dissertation (Master’s in nursing) – Post-graduation Program in Nursing at the Health Sciences Center from the Federal Univiersity of Paraíba, João Pessoa, Paraíba, Brazil. Introduction: Information is the source of knowledge that provides several points of view for interpretation of phenomena and construction of knowledge. Based on this assumption, information systems have the purpose of offering knowledge to serve as a basis for the effective management of services. Objectives: To understand how the manager perceives the quality of information produced by e-SUS AB; To describe the influence of this information on the practice of health managers and to identify the difficulties faced in the use of e-SUS AB. Method: Exploratory-descriptive study, with a qualitative approach, using as theoretical and methodological reference the Grounded Theory. The participants of the research were 16 health managers from the sanitary districts of the municipality of João Pessoa-PB, Brazil. Data collection was performed through the application of a semi-structured interview script. Data analysis was performed through three coding steps: open, axial and selective. Results: Based on the analysis of the data, we identified the phenomenon 1 - Understanding the perception about the quality of information produced by e-SUS AB and its influence on the work process of health managers and the phenomenon 2 - Pointing difficulties and perspectives in adaptation And search for improvement of e-SUS AB. Based on the analysis of the categories and phenomena we tried to describe the managers' understanding of the theme, identifying positive and negative points of the experience with e-SUS AB. In making the connection between the two phenomena emerged the central category of the study: Searching for the quality of information produced by e-SUS AB: influences, difficulties and perspectives of health managers. Conclusion: It was verified that health managers in the city of João Pessoa-PB are concerned with using quality information to support decision-making, strengthen strategies for the implementation of e-SUS AB, and raise the standard of services Provided to the population.